Defining the Effective Threshold using Modified Wigner-Hough Transform in FMCW-Signal Detection - Erdogan, A. Yasin; Gulum, Taylan O.; Durak-Ata, Lutfiye; Yildirim, Tulay; Pace, Phillip E. (IEEE, 2013)
In response to the fast improvements in antiradiation systems and electronic attack systems, radar systems began exploiting low power, wide-band, frequency agility techniques to decrease their intercept probability. This increase in the use of low probability of intercept (LPI) waveforms in current radar systems enforces the intercept receiver to use sophisticated signal processing algorithms. It has been observed that, the threshold applied on Wigner-Ville images has an impact on the efficiency of Wigner-Hough based algorithms. In this study, we investigated the effect of the WV threshold on signals with SNRs ranging from [0dB, -9dB], and suggested that the optimum threshold is between 20-40% of the max WV image energy intensity.
Keywords: Wigner-Ville; threshold; LFM-signal; Wigner-Hough Transform; Engineering; Telecommunications